2008
DOI: 10.1126/science.1160799
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic(III) Fuels Anoxygenic Photosynthesis in Hot Spring Biofilms from Mono Lake, California

Abstract: Phylogenetic analysis indicates that microbial arsenic metabolism is ancient and probably extends back to the primordial Earth. In microbial biofilms growing on the rock surfaces of anoxic brine pools fed by hot springs containing arsenite and sulfide at high concentrations, we discovered light-dependent oxidation of arsenite [As(III)] to arsenate [As(V)] occurring under anoxic conditions. The communities were composed primarily of Ectothiorhodospira-like purple bacteria or Oscillatoria-like cyanobacteria. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
167
0
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 208 publications
(179 citation statements)
references
References 26 publications
6
167
0
4
Order By: Relevance
“…Recently, anaerobic As(III) oxidation was found in the haloalkaliphilic bacterium Alkalilimnicola ehrlichii strain MLHE-1 and the photosynthetic purple sulfur bacterium Ectothiorhodospira sp. strain PHS-1 (Kulp et al, 2008;Zargar et al, 2010), which was suggested to be conducted by a new arsenite oxidase clade, ArxA (Zargar et al, 2012), though no information is presently known on the this enzyme's functioning (van Lis et al, 2013). Through these processes, As speciation and bioavailability are altered, affecting its toxicity, environmental behavior and fate in the environment, and also its accumulation into food crops (such as rice) (Jia et al, 2014(Jia et al, , 2013Stolz and Oremland, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, anaerobic As(III) oxidation was found in the haloalkaliphilic bacterium Alkalilimnicola ehrlichii strain MLHE-1 and the photosynthetic purple sulfur bacterium Ectothiorhodospira sp. strain PHS-1 (Kulp et al, 2008;Zargar et al, 2010), which was suggested to be conducted by a new arsenite oxidase clade, ArxA (Zargar et al, 2012), though no information is presently known on the this enzyme's functioning (van Lis et al, 2013). Through these processes, As speciation and bioavailability are altered, affecting its toxicity, environmental behavior and fate in the environment, and also its accumulation into food crops (such as rice) (Jia et al, 2014(Jia et al, , 2013Stolz and Oremland, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the arsenic seems to have been present at much higher concentrations in the ancient Earth's crust than it is today (Oremland et al, 2009). The characteristics and biochemical nature of the ancient arsenic metabolism is subject of an ongoing debate (Kulp et al, 2008;Schoepp-Cothenet et al, 2009). Members of both Bacteria and Archaea encode aio genes for As(III) oxidation, which could be used for chemolithotrophic growth (van Lis et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent follow-up characterizations of this organism and this process failed to materialize; however, approximately 2 decades later, Santini et al (52) described the isolation and initial characterization of a Rhizobiumlike bacterium (strain NT-26) that could grow chemolithoautotrophically with As III as a sole electron donor for energy generation and with CO 2 as a sole carbon source. Soon thereafter, and in part stimulated by the massive arsenic poisoning disaster in Bangladesh (2), a series of studies initiated the characterization of microbial As III oxidation in natural environments, including geothermal springs (9,11,12,17,19,24,25,35,51) and soils (41); in mining-contaminated environments (6,13,40); and, most recently, in anoxic photosynthesis (21,33 (28,31) indicated the role and importance of the sensor kinase AioS and its putative regulatory partner AioR (a bacterial enhancer binding protein), direct proof of these two proteins working together as part of a putative As III signal perception and transduction cascade was just recently provided by Sardiwal et al (54), who demonstrated the autophosphorylation of an AioS component and the AioS-specific phosphorylation of AioR. Recently, our work has expanded this regulatory model to now include a third component, AioX, which is a periplasmic As III binding protein that is also essential for aioBA expression (39 …”
mentioning
confidence: 99%